2000
DOI: 10.1111/j.8755-8920.2000.430204.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β Down‐Regulates the Oxytocin Receptor in Cultured Uterine Smooth Muscle Cells

Abstract: IL-1 down-regulates the uterine oxytocin receptor in a time- and dose-dependent fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 18 publications
2
27
1
2
Order By: Relevance
“…In the human adrenal gland, however, glucocorticoids inhibit 17␣-hydroxylase activity, which is involved in dehydroepiandrosterone sulfate production [39]. Interleukin-1␤ (inflammatory cytokine) and oxytocin itself each reduced the OTR mRNA level in human myometrial cells and tissues [40][41][42][43][44]. Interleukin-6 had various effects on the expression of OTR mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In the human adrenal gland, however, glucocorticoids inhibit 17␣-hydroxylase activity, which is involved in dehydroepiandrosterone sulfate production [39]. Interleukin-1␤ (inflammatory cytokine) and oxytocin itself each reduced the OTR mRNA level in human myometrial cells and tissues [40][41][42][43][44]. Interleukin-6 had various effects on the expression of OTR mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…estrogen, progesterone), inflammatory cytokines (e.g. interleukin1b, interleukin-6), OT, and lactation suckling influence the expression of OTR at the mRNA or protein level (Phaneuf et al 1997, Phaneuf et al 1998, Fang et al 2000, Rauk & Friebe-Hoffmann 2000, Helmer et al 2002. However, the influence of these factors was limited in the present study using in vitro experiments under non-hormonal conditions.…”
Section: Discussionmentioning
confidence: 80%
“…Inositol triphosphate production and intracellular free calcium were reduced by 75% after IL-1 treatment. In comparison, the concentration of oxytocin receptors per cell was reduced by 90% after 24 h of IL-1 treatment [9]. This impairment in signaling appears to be solely due to a reduction in oxytocin receptors and not through changes in second-messenger signaling proteins.…”
Section: Discussionmentioning
confidence: 84%
“…Molnar et al [8] demonstrated that IL-1 treatment of myometrial tissues for a short duration increases arachidonic acid (AA) release and potentiates oxytocin-mediated contractility. In contrast, we have shown that prolonged exposure of myometrial cells to IL-1 results in down-regulation of the oxytocin receptor [9]. Following 24 h of IL-1 treatment, myometrial cells have 90% fewer oxytocin receptor binding sites.…”
Section: Introductionmentioning
confidence: 70%